An all-digital approach for versatile hybrid entanglement generation. (1st May 2022) - Nape, Isaac; de Oliveira, André G; Slabbert, Donovan; Bornman, Nicholas; Francis, Jason; Souto Ribeiro, Paulo H; Forbes, Andrew
Abstract: Hybrid entangled states exhibit non-local correlations between photons with independent degrees of freedom and are currently gaining much interest. In particular, hybrid entanglement between polarisation and spatial modes of two photons are promising candidates for future heterogeneous quantum channels, but their versatility is limited by current generation methods that rely on static elements. Here, we present a technique that exploits polarisation and spatial mode dependent phase modulation in an all-digital approach using spatial light modulators. We show that we can tailor hybrid entangled states using spatial modes with Cylindrical and Cartesian symmetry, making our approach flexible, dynamic, and adaptable.